Sekwencyjność w liberalizacji zewnętrznych stosunków państw a globalizacja - Żukrowska, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Liberalization of external economic relations of states played an important role in past economic relations and it is expected that this role will increase following deepening of liberalization in the future. The paper defines liberalization, shows in which fields it is introduced and what is its role for economic systems of states. It comments organizational structures, which support liberalization, and points at technical solutions, which are applied here, linked with sequencing of the process and depth of applied moves. The role of liberalization sequencing is stressed as an precondition enhancing catching up in development strategies of developing economies, what enables cutting the time needed for that process. Moreover, liberalization of global trade is considered as a solution, which leads to creation of conditions for sustainable growth. Economic liberalization proceeds on all continents, while the strongest impulses are given by two most developed markets: the EU and USA. Liberalization is conducted on different levels of international co-operation: globally by the WTO, subregionally by countries and/or regional integration organizations with regional organizations, regionally within integration organizations and between two states/markets. Thus liberalization can be conducted multilaterally. bilaterally or autonomously (without reciprocity). Liberalization is conducted within two models of trade co-operation: within customs unions or free trade zones. Customs unions can lead towards monetary integration in the future. Most of the free trade zones introduce also free movement of capital. World trade liberalization is supposed to lead in long perspective to liberalize international economic relations following the model of internal market of the EU. Visions that liberalization hinders economic growth are still quite popular, despite all the proofs showing the opposite, politicians often use legal and institutional solutions, which can stimulate this process in their economies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 397-417